Evidence-based improvisation: Facing the challenges of cervical cancer care in Uganda - Megan Swanson; Stefanie Ueda; Lee-may Chen; Megan J. Huchko; Carol Nakisige; Jane Namugga (Elsevier, 2018)
There is significant disparity in the prevalence of cervical cancer globally, with low- and middle-income countries (LMICs) shouldering a disproportionate share of disease incidence and an even greater proportion of morbidity and mortality. Available resources for diagnosis, treatment and palliation of cervical cancer are inversely related to per capita income. While prevention and screening remain public health priorities, given the large number of women affected by cervical cancer, expanding treatment capacity should be included in any evidence-based intervention plan. Uganda, a country with a high incidence of cervical cancer, serves as a representative case study in terms of the challenges of diagnosis and access to treatment in sub-Saharan Africa. Providers and patients in Uganda are challenged by late presentation to care, limited training opportunities, cost-prohibitive diagnostic studies, insufficient access to gold-standard treatment, and under-utilized palliative care services. This review highlights the ways in which Uganda's experience is typical of the continent at large, as well as areas where Uganda is unique. We describe the ways in which a small but dedicated group of gynecologists carefully use limited evidence and available resources creatively to provide the best possible care for their patients. We show that improvisation, albeit evidence-based, is central to the nature and success of oncology care in Africa (Livingston, 2012). We argue that a "recalibrated global response" (Farmer et al., 2010), particularly stressing the expansion of radiotherapy capabilities, could dramatically improve cancer care and outcomes for women in Uganda as well as in LMICs globally.